PARTISIPASI MASYARAKAT DALAM PENGELOLAAN DANA DESA (Studi di Desa Marga Sakti Kecamatan Padang Jaya Kabupaten Bengkulu Utara) - fikri, muhammad; Supardi Mursalin; Citra Liza (JSE: Jurnal Sharia Economica, 2026)
This study aims to identify the forms of community participation in the management of village funds in Marga Sakti Village and to assess whether the management process has been carried out transparently, accountably, and in accordance with community needs. The research uses a descriptive qualitative method with a descriptive approach and applies a purposive sampling technique, in which respondents are deliberately selected based on their understanding of village fund management. A total of 10 participants were involved, consisting of village officials, community leaders, youth, and local residents. The results show that the level of community participation in Marga Sakti Village varies at each stage of fund management. Participation is relatively good during the planning and implementation stages, while at the supervision and evaluation stages, it still needs improvement. Overall, the management of village funds in Marga Sakti Village has been carried out quite transparently and accountably; however, greater community involvement in all stages is needed to make fund management more effective and aligned with community needs.